Role of Russia’s and China’s Higher Educational Institutions in the Development of Innovation Educational Clusters - Y. G. Gertsik (Ekonomika Nauki)
The article is devoted to one of the most perspective mechanisms of innovation implementation in Russia and China – in the form of innovation educational clusters. The leading role of higher educational institutions is underlined in formation of innovative economy and high-tech projects, as well as in the decision of previously established and newly emerging constraints associated with global processes in the world economy. Based on the review and analysis of its results, the authors formulate proposals for applying the existing experience of implementing the cluster approach with the direct participation of higher education institutions in the creation of international innovative educational clusters for the formation of joint projects in the most promising industries and technologies, in particular, in the medical industry and pharmaceuticals. The relevance of the research is due to the need for further development of educational and scientific ties, trade and economic relations between Russia and China, increasing the competitiveness of both national economic systems as a whole, and high-tech enterprises of the two countries in domestic and global markets.